2020
DOI: 10.1021/acs.orglett.0c01186
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Protein Cascade Reaction for the Regioselective Synthesis of Quinoxalines

Abstract: In this work, an efficient dual-protein (lipase and hemoglobin) system was successfully constructed for the regioselective synthesis of quinoxalines in water. A set of quinoxalines were obtained in high yields under optimal reaction conditions. This dual-protein method exhibited a regioselectivity higher than those of previously reported methods. This study not only provides a green and mild strategy for the synthesis of quinoxalines but also expands the application of lipase and hemoglobin in organic synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…However, the regioselective synthesis of multisubstituted quinoxalines is impractical using these methods. In contrast, Li, Wang, and their coworkers recently reported a dual-protein-catalyzed regioselective synthesis of 2,3,6-/2,3,7-trisubstituted quinoxalines, which exhibited a higher regioselectivity (i.e., up to 77:23) than those achieved using previous methods …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the regioselective synthesis of multisubstituted quinoxalines is impractical using these methods. In contrast, Li, Wang, and their coworkers recently reported a dual-protein-catalyzed regioselective synthesis of 2,3,6-/2,3,7-trisubstituted quinoxalines, which exhibited a higher regioselectivity (i.e., up to 77:23) than those achieved using previous methods …”
Section: Introductionmentioning
confidence: 89%
“…In contrast, Li, Wang, and their coworkers recently reported a dual-protein-catalyzed regioselective synthesis of 2,3,6-/2,3,7trisubstituted quinoxalines, which exhibited a higher regioselectivity (i.e., up to 77:23) than those achieved using previous methods. 14 We previously reported the one-pot three-component synthesis of 2,3-disubstituted quinoxalines (Scheme 1). 15 This route commenced with the N-heterocyclic carbene (NHC)-catalyzed aroylation of imidoyl chlorides with aldehydes to afford iminoethanones, followed by their hydrolysis to 1,2-diketones, which were subsequently reacted with o-phenylenediamine to obtain 2,3-disubstituted quinoxalines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many studies have reported the formation of carbon‐carbon and carbon‐heteroatom bonds, such as Michael addition, perhydrolysis, aldol addition, Morita‐Baylis‐Hillman reaction, and Knoevenagel condensation [13–16] . Based on these findings, many lipase‐catalyzed MCRs have been reported to synthesize complex bioactive molecules, and these findings have widened the application of lipase [17–19] . However, most of these enzymatic MCRs have encountered problems of long reaction time and the utilization of volatile organic solvents.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16] Based on these findings, many lipasecatalyzed MCRs have been reported to synthesize complex bioactive molecules, and these findings have widened the application of lipase. [17][18][19] However, most of these enzymatic MCRs have encountered problems of long reaction time and the utilization of volatile organic solvents.…”
mentioning
confidence: 99%
“…However, the existing methods often suffer from at least one of the following limitations, such as requirement of highly functionalized substrates, 7 multi-step synthetic sequences, 8 lack of structural diversity of target products as well as harsh/complex reaction conditions with low atom-/step-efficiency. 9 For example, 3aa could be synthesized from the corresponding lactam i using Berzelius reagent (P 2 S 5 ) 12 b or from chloride ii , 1 c which was obtained from ii using POCl 3 . It should be noted that both of these phosphorus reagents were highly reactive, moisture sensitive and low functional group tolerant.…”
mentioning
confidence: 99%